Effect of Microbial-Induced Calcite Precipitation on Surface Erosion and Scour of Granular Soils: Proof of Concept. Issue 1 (January 2017) - Bao, Ruotian; Li, Junhong; Li, Lin; Cutright, Teresa J.; Chen, Long; Zhu, Jiahua; Tao, Junliang
Erosion is relevant to a variety of infrastructure problems such as bridge scour, roadway shoulder erosion, coastal erosion, and riverbank and slope stability. This research investigated the feasibility of using microbial-induced calcite precipitation (MICP) as an erosion countermeasure. MICP is a natural phenomenon in which calcite precipitation occurs as a consequence of microbial metabolic activity. The precipitated calcite modifies the soil fabric and provides an additional bonding force between soil particles. In this paper, a preliminary experimental study on the erosional behavior of MICP-treated sand is presented. A standard soil, Ottawa graded sand, was treated with a bacterium (Sporosarcina pasteurii) in a full-contact reactor-one in which the soil in a fabric mold was fully immersed in the bacteria and cementation solution. The morphologies and crystalline structures of the precipitated calcite in porous sediments were characterized using microscopic imaging techniques. The treated soil samples were tested in a flume to investigate the erosional behavior; both surface erosion and bridge scour tests were conducted. Although the untreated soil is highly erodible, the erosion of the treated sand was found to be negligible under the circumstances of the test; however, some concerns were raised regarding practical applications. Efforts will be made in the future to identify alternative treatment procedures that are more applicable to the field.